1997
DOI: 10.1073/pnas.94.2.634
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α/β inhibition of interleukin 12 and interferon-γ productionin vitroand endogenously during viral infection

Abstract: Interferon ( Interleukin 12 (IL-12) is a heterodimeric cytokine with many functions including induction of interferon (IFN)-␥ by natural killer (NK) cells and generation of T helper 1 (Th1) cells producing IFN-␥ (1). The role of IL-12 in promoting endogenous protective immune responses to viral infections, however, is only beginning to be understood (2, 3). Our studies of IL-12 administration during lymphocytic choriomeningitis virus (LCMV) infections of mice have demonstrated that high concentrations of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
183
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(206 citation statements)
references
References 36 publications
20
183
3
Order By: Relevance
“…IFN-␣ and IFN-␤ were found to increase IL-12 mRNA in human macrophages (4) and up-regulate the expression of the IL-12R ␤2 chain in CD4 ϩ T cells (33). However in other studies, type I IFNs suppressed IL-12 production in a mixed leukocyte population and in dendritic cells (23,34). Further support for an inhibitory role of class I IFNs comes from in vivo studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…IFN-␣ and IFN-␤ were found to increase IL-12 mRNA in human macrophages (4) and up-regulate the expression of the IL-12R ␤2 chain in CD4 ϩ T cells (33). However in other studies, type I IFNs suppressed IL-12 production in a mixed leukocyte population and in dendritic cells (23,34). Further support for an inhibitory role of class I IFNs comes from in vivo studies.…”
Section: Discussionmentioning
confidence: 90%
“…Further support for an inhibitory role of class I IFNs comes from in vivo studies. In virally infected mice, endogenously expressed IFN-␣␤ inhibited the ability of LPS to induce IL-12, while neutralization of IFN-␣␤ enhanced IL-12 and IFN-␥ production (34). Lastly, Wang et al (35) demonstrated that IFN-␤ inhibits IL-12 production in Staphylococcus aureus Cowan-plus IFN-␥-stimulated human PBMC in an IL-10-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that during murine cytomegalovirus and lymphocytic choriomeningitis virus infection, endogenous IFN-␣␤ inhibit IL-12 and IFN-␥ production (54). The low levels of IFN-␣␤ in C. pneumoniae-infected mice are probably not sufficient for inhibition of IL-12, which therefore governs IFN-␥ production in vivo (33).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that IFN-␣␤ function to inhibit endogenous IL-12 expression during LCMV infection (11). In addition, 2 days after viral infections, IFN-␣␤ induce a refractory state in which NK cell IFN-␥ responses to IL-12 and anti-CD3-elicited IFN-␥ production from splenocytes are inhibited (69).…”
Section: Discussionmentioning
confidence: 99%